Computational modeling of oscillating fins that "catch and release" targeted nanoparticles in bilayer flows. Issue 5 (18th December 2015) - Liu, Ya; Bhattacharya, Amitabh; Kuksenok, Olga; He, Ximin; Aizenberg, Michael; Aizenberg, Joanna; Balazs, Anna C.
Abstract : A number of physiological processes in living organisms involve the selective "catch and release" of biomolecules. Abstract : A number of physiological processes in living organisms involve the selective "catch and release" of biomolecules. Inspired by these biological processes, we use computational modeling to design synthetic systems that can controllably catch, transport, and release specific molecules within the surrounding solution, and, thus, could be harnessed for effective separation processes within microfluidic devices. Our system consists of an array of oscillating, microscopic fins that are anchored onto the floor of a microchannel and immersed in a flowing bilayer fluid. The oscillations drive the fins to repeatedly extend into the upper fluid and then tilt into the lower stream. The fins exhibit a specified wetting interaction with the fluids and specific adhesive interactions with nanoparticles in the solution. With this setup, we determine conditions where the oscillating fins can selectively bind, and thus, "catch" target nanoparticles within the upper fluid stream and then release these particles into the lower stream. We isolate the effects of varying the wetting interaction and the fins' oscillation modes on the effective extraction of target species from the upper stream. Our findings provide fundamental insights into the system's complex dynamics and yield guidelines for fabricating devices for the detection and separation of target molecules from complex fluids.